2007
DOI: 10.1111/j.1471-0528.2006.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and biological markers of stress and bacterial vaginosis in pregnant women

Abstract: Objectives To determine whether stress is associated with risk of bacterial vaginosis (BV) in pregnant women.Design Prospective cohort study.Setting The prenatal care clinics at the University of North Carolina. The residents' clinic sees mostly government-insured and uninsured women, and the physicians' clinic sees mostly those with private health insurance.Population A total of 897 women gave samples for BV analysis. Study participants were 22% African-American, 68% white; 24% unmarried and 44% nulliparous. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 25 publications
5
17
0
1
Order By: Relevance
“…This association is consistent with several studies conducted in developing countries, particularly in Asia [80Á83]. Many studies demonstrate an association between stress or anxiety and an increased susceptibility to many infectious diseases including reproductive tract infections [84,88]. Stress-induced activation of the hypothalamic-pituitary-adrenal (HPA) axis which influences the immune system has been purported to mediate the relationship between stress and infection [84,85].…”
Section: Discussionsupporting
confidence: 82%
“…This association is consistent with several studies conducted in developing countries, particularly in Asia [80Á83]. Many studies demonstrate an association between stress or anxiety and an increased susceptibility to many infectious diseases including reproductive tract infections [84,88]. Stress-induced activation of the hypothalamic-pituitary-adrenal (HPA) axis which influences the immune system has been purported to mediate the relationship between stress and infection [84,85].…”
Section: Discussionsupporting
confidence: 82%
“…It is possible that working women experience more psychosocial stress, which other authors have suggested increases the risk of bacterial vaginosis by lowering their immune function. 26 Using an IUD and being nulliparous were found to be associated with bacterial vaginosis in our study. A biological explanation for this could that the presence of a neutrophil elastase inhibitor known as secretory leukocyte protease inhibitor (SLPI) in human cervical mucosa.…”
supporting
confidence: 49%
“…Three studies found that problem-focused coping styles, such as problem-solving, planning and preparation, are associated with greater pregnancy-related distress (Faisal-Cury et al, 2012; Hamilton & Lobel, 2008; Yali & Lobel, 1999), whereas a fourth found that active coping styles were associated with fewer depressive symptoms (Wells, Hobfoll, & Lavin, 1997). John Henryism, an effortful coping style, has been linked to greater likelihood of exercise during pregnancy among African-American pregnant women (Orr, James, Garry, & Newton, 2006), but it was also more strongly associated with bacterial vaginosis than any other stress-related measure in 1,587 pregnant women in North Carolina (Harville, Savitz, Dole, Thorp, & Herring, 2007). The results of the latter study suggest a link between coping processes and immune function, although this association was no longer statistically significant in analyses that controlled for age, income, and race.…”
Section: Resultsmentioning
confidence: 99%